Testing the Purchasing Power Parity Hypothesis: Case of ASEAN Economies - Bekő, Jani; Boršič, Darja (Naše gospodarstvo/Our economy, 2022)
We examine the purchasing power parity (PPP) hypothesis of 10 members of ASEAN. A battery of panel unit root tests is employed on data series from January 1995 to January 2018 in order to search for validity of PPP in the period before the Great Recession and in the post-crisis period. All the calculations are based on four numeraire currencies: Chinese yuan (CNY), Japanese yen (JPY), US dollar (USD), and the euro (EUR). First, following the outcome of the present study for ASEAN countries, the PPP holds mostly with respect to CNY rates. Second, for the post-financial crisis period, our research proves conclusively that the PPP supposition is predominantly valid between the currencies of ASEAN countries and EUR rates. The sample of countries in the study is limited to the ASEAN group of economies. Based on the evaluated parity conditions, the emergence of global economic crisis brought about significant currency shifts in the ASEAN. The selection and testing of a broader range of numeraire currencies is vital to provide empirical underpinning for PPP notion.